THE INHIBITION OF STEEL CORROSION IN ACIDIC SOLUTIONS BY A NEW SCHIFF BASE - Bakirhan, N. K.; Asan, A.; Colak, N.; Sanli, S. (Journal of the Chilean Chemical Society, 2016)
The inhibition effect of 2,2’- (((thiobis (4,1 phenylene)) bis(azanylylidene)) bis(methanylyidene)) bis(4-methoxyphenol) (BIS-IMIN) on the corrosion behavior of 304-stainless steel (SS) in 0.5 M HCl solution was studied by electrochemical impedance spectroscopy (EIS) and potentiodynamic polarization techniques. SEM, FT-IR, 1H-NMR, 13C-NMR methods used for characterization of BIS-IMIN. Potentiodynamic polarization curves indicated that BIS-IMIN act as mixed type inhibitor. The adsorption of the inhibitor was more suited with the Langmuir adsorption isotherm and kinetic parameters Kads, ΔGads, Ea , ΔHads, ΔSads were determined at room temperature. The results showed that BIS-IMIN performed well inhibiting effect for the corrosion of the SS.